Left ventricular remodeling in normotensive Wistar rats exposed to intermittent hypoxia of different duration - Yu. M. Kolesnyk; M. Yu. Kolesnyk; O. V. Hancheva; M. I. Isachenko (Patologìâ)
Intermittent hypoxia has been studied for many years as a promising non-pharmacological method of cardiovascular disease prevention. Hypoxic effects are accompanied by structural and functional changes in the myocardium. There is a direct link between the duration of hypoxic exposures and the severity of left ventricular myocardial remodeling. A range of histochemical markers of myocardial remodeling (cardiotrophin-1, titin, collagen type 1, annexin V) characterizing parenchymal-stromal relationships in the myocardium has shown high informativeness and prognostic value.